Sustained censorship in IN (2026-06) (India) - Voidly (2026)
CRITICAL severity censorship detected in India. Confidence: 80%. Data sourced from OONI.
Censorship Incident ID: IN-2026-0165
Keywords: censorship; IN; censorship; critical